The Importance of Realizing Fair, Beneficial and Definitive Criminal Case Resolution Based on the Principles of Deliberation and Consensus - Sastrawan, Rusydi; Usman, Usman; Herlambang, Herlambang (PT. Hafasy Dwi Nawasena, 2024)
The principle of Musyawarah Mufakat is the basis or basic law for deliberation, urun rembug or joint discussion to resolve problems to finally make decisions that are agreed upon or agreed upon or find solutions to resolve problems that are mutually agreed upon. The culture of deliberation, as a value system lived by the Indonesian people, is a spirit for each party in the deliberation to resolve conflicts, for example, will try to reduce their stance so that a meeting point that is beneficial to all parties can be reached, which leads to consensus. What is decided in the deliberation to resolve the conflict slowly develops into customary law. This research will discuss how the deliberation principle of consensus is regulated in the settlement of criminal cases to realize justice, certainty and legal benefits, and what is the urgency of the deliberation principle of consensus in the settlement of criminal cases to realize justice, certainty and legal benefits. This research uses normative juridical research methods using a statutory approach (state approach), case approach (case approach), comparative approach (comparative approach), conceptual approach (conceptual approach). Based on the results of the research, the principle of deliberation has been applied for a long time, both in the old order, the new order and at this time, although not every stage of the law enforcement process has been carried out, especially at the most crucial stage, namely investigation and prosecution. Law Number 1 of 2023 concerning the new Criminal Code has regulated the enactment of laws that live and develop in society so that it is deemed necessary and very important for the Criminal Procedure Law in the future (Ius Constituendum) to regulate the settlement of criminal cases based on the principle of consensus to follow up on the material law that has been passed and is very irrelevant to criminal law enforcement in Indonesia if Law Number 8 of 1981 concerning the Criminal Procedure Code remains in effect after the enactment and enactment of the new Criminal Code.